2020
DOI: 10.1088/1361-6668/ab6958
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of airgap influence on DC voltage generation in a dynamo-type flux pump

Abstract: High-temperature superconducting (HTS) Flux pumps are promising devices to maintain steady current mode in HTS magnets or to energize rotor windings in motors and generators in a contactless way. Among different types of flux pumps, the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 36 publications
(89 reference statements)
3
41
0
Order By: Relevance
“…The gap dependence of the open-circuit voltage computed by Ghabeli and Pardo [14] also agrees with experiments. In [14], it is also shown that this voltage is independent of the critical current density, Jc, when the superconductor is fully penetrated by supercurrents. Since these overcritical eddy currents must recirculate in the HTS wire, and can co-exist with a transport current, the wire width is a key parameter and [15] shows that this should be sufficiently large so that the eddy and transport currents do not drive the full width of the wire into the fluxflow regime.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The gap dependence of the open-circuit voltage computed by Ghabeli and Pardo [14] also agrees with experiments. In [14], it is also shown that this voltage is independent of the critical current density, Jc, when the superconductor is fully penetrated by supercurrents. Since these overcritical eddy currents must recirculate in the HTS wire, and can co-exist with a transport current, the wire width is a key parameter and [15] shows that this should be sufficiently large so that the eddy and transport currents do not drive the full width of the wire into the fluxflow regime.…”
Section: Introductionsupporting
confidence: 81%
“…The DC output voltage obtained from an HTS dynamo arises naturally from a local rectification effect caused by overcritical eddy currents [7][8][9][10][11][12]: an effect that has been observed in HTS materials as far back as Vysotsky et al [13]. The gap dependence of the open-circuit voltage computed by Ghabeli and Pardo [14] also agrees with experiments. In [14], it is also shown that this voltage is independent of the critical current density, Jc, when the superconductor is fully penetrated by supercurrents.…”
Section: Introductionsupporting
confidence: 72%
“…High-T c superconducting (HTS) dynamos [1][2][3][4][5][6][7][8][9][10][11][12][13] and other similar HTS "flux pumps" [14][15][16][17][18][19][20][21][22] have been receiving continuing attention recently, as they offer a potential solution to the dc current-injection problem in a wide range of superconducting machines [23] and magnets [24,25]. Specifically, the HTS dynamo is of interest for its predicted output produced by a HTS dynamo arises naturally from Maxwell's laws [12] when applied to a situation in which eddy currents flow in a thin sheet exhibiting a highly nonlinear local resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several numerical models have been developed, which can be categorized into two groups. The first group models the open-circuit mode, where the output current is zero [22][23][24][25][26][27][28]. All of these models could explore the essential mechanism of the flux pump to deliver a DC voltage by the assumption of constant critical current density J c for the HTS tape characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…All of these models could explore the essential mechanism of the flux pump to deliver a DC voltage by the assumption of constant critical current density J c for the HTS tape characteristic. However, only some of them considered J c (B, θ) dependency, which enable the models to generate an output voltage much closer to reality and comparable to experiments [22,23,25]. The second group presented in [29] and [30] are capable of also modeling the HTS dynamo with an imposed DC transport current; using these models, the I-V curves of the flux pump and the associated effective resistance at different frequencies could be obtained.…”
Section: Introductionmentioning
confidence: 99%